Optimising PID controller using slope variation method for positioning radio telescope - Mohamad Zaber, Nursaida; Ishak, Asnor Juraiza; Che Soh, Azura; Hassan, Mohd Khair; Ishak, Asnor Nadirah (Universiti Putra Malaysia Press, 2017)
Radio telescope is an application that requires a precise position control as it should point to the exact coordinate so that it could receive the desired signal. The main idea of this paper is to optimise the PID controller by introducing slope variation method in order to control the position of a radio telescope. This proposed method is also validated with the presence of disturbance, such as wind gust disturbance with different speed amplitude. The results indicate that the proposed optimisation method has a better result with no overshoot and able to attenuate wind gust disturbance when compared with conventional PID controller.